Perlindungan Hukum Terhadap Anak Sebagai Saksi Pada Tahap Penyidikan Berdasarkan Undang-Undang Nomor 11 Tahun 2012 Tentang Sistem Peradilan Pidana Anak - jprautor, jprautor (JURNAL PROPERTY RIGHTS, 2015)
The protection of children as witnesses are all activities to ensure and protect children and their rights as a witness in order to provide information for the purpose of investigation, prosecution, and trial court examination of a criminal case is heard, seen and / or experienced themselves. Problems studied is whether the juvenile criminal justice system already reflects and manifests a sense of justice for children as witnesses and the rights of children as witnesses at this stage of the investigation that must be met by the police and how the process protection.The study design is a juridical empirical study design, which is located in the Resort Police Malang City. Procedures and techniques taking samples using purposive sampling. The primary data collection techniques traced and obtained through interviews and direct observation by the police in particular to the official PPA Unit (Ministry of Women and Children). Analysis of data obtained through interviews, field observation, and data from the literature study will explain the real situation.The protection afforded by the investigator to the child as a witness is medical rehabilitation and social rehabilitation, both within the institution and outside the institution. Safety assurance, both physically, mentally and socially and ease in obtaining information about the development of the case. Rights of the child as a witness in the investigation stage in Malang City Police among others, keep the identity of the child as a witness; mentoring by parents, guardians and psychologists; and inform the witness about the purpose of his calling. While the process of protection at the time of the call and inspection.Based on the description of the previous chapter it can be concluded that the protection provided by the investigators Resort Malang both the rights of children as witnesses and protection processes are still many who have constraints, for example the revision or improvement of the Law on juvenile criminal justice system will be in vain , if not accompanied by adequate infrastructure and should be increased when examination of children as witnesses by investigators Resort Malang City. Problems short time troublesome investigations to adjust school hours child witnesses to be called and questioning.